2017
DOI: 10.1037/neu0000371
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Parkinson’s disease display a dopamine therapy related negative bias and an enlarged range in emotional responses to facial emotional stimuli.

Abstract: Our results indicate a relationship between emotional responses, PD, and dopaminergic therapy, in which PD per se is associated with stronger emotional responses, whereas LED levels are negatively correlated with the strength of emotional responses. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Studies in healthy individuals showed that distinct visual scanning patterns emerge for each emotion, such as a focus on the mouth of happy faces and the eyes of sad and angry faces [ 28 ] which is present even when the subject searches for evidence of a specific emotion in neutral faces [ 29 ]. This goal-driven strategy in visual scanning for emotion recognition seems to deteriorate with cognitive decline in PD-MCI, since PD-MCI patients show a shift to the middle part of the face as well as an overall deterioration of focus on the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in healthy individuals showed that distinct visual scanning patterns emerge for each emotion, such as a focus on the mouth of happy faces and the eyes of sad and angry faces [ 28 ] which is present even when the subject searches for evidence of a specific emotion in neutral faces [ 29 ]. This goal-driven strategy in visual scanning for emotion recognition seems to deteriorate with cognitive decline in PD-MCI, since PD-MCI patients show a shift to the middle part of the face as well as an overall deterioration of focus on the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature indicates that subjective appraisal of emotional intensity may also be altered in PD patients. Several studies have shown that PD patients exhibit negativity bias, or a stronger emotional response to negative emotional stimuli (De Risi et al, 2018;Hälbig et al, 2011;Lundqvist et al, 2017). In a study by Lundqvist and colleagues (2017), for example, PD patients displayed a negativity bias in the form of more negative valence ratings for disgusted, fearful, and sad faces.…”
Section: Changes In Emotion Regulation In Early Pd Progressionmentioning
confidence: 99%
“…Moreover, most of these studies have been disproportionately focused on negative emotions, or include significantly fewer measures of positive emotion in comparison to negative emotions (Gray & Tickle-Degnen, 2010;Péron et al, 2012). Studies which have included positive emotion categories, and analysis for emotional range, have shown a more general increase in emotional range so that negative stimuli are rated as more strongly negative, and positive stimuli more strongly positive in PD patients compared to HC (Lundqvist et al, 2017). Hence, the common tendency to rely primarily on negative stimuli could potentially contribute to the false appearance of a negativity bias among PD patients.…”
Section: Changes In Emotion Regulation In Early Pd Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on emotion processing in PD indicates that recognition of and responses to emotional stimuli are biased, though results have often been conflicting (Gray & Tickle-Degnen, 2010; Lundqvist et al, 2017). Some studies have found general evidence of emotional deficits in PD patients compared to healthy controls (HC), while others have found no significant differences between the groups (Gray & Tickle-Degnen, 2010; Hälbig et al, 2011; Ille et al, 2016; Péron et al, 2012; Wabnegger et al, 2015).…”
mentioning
confidence: 99%